Thermal and mechanical properties of lightweight concretes produced with pumice and tragacanth - Akpinar, Ebru Kavak; Kocyigit, Fatih (Taylor & Francis Ltd, 2016)
This study was carried out to determine the possibilities of using tragacanth and pumice aggregate in lightweight concrete producing. The samples were produced with mixture combinations of materials such as pumice, tragacanth, and cement. The prepared material samples were subjected to some tests such as thermal conductivity, compressive strength, tensile strength, abrasion loss, and water absorption (WA). It was determined that density, thermal conductivity, compressive strength, tensile strength, abrasion loss, and WA varied as 0.728-1.772g/cm(3); 0.177-0.433W/mK; 6.1-258.80kg/cm(2); 2.73-17.81kg/cm(2); 0.0-19.9%; and 20-56.8%, respectively. The results showed that the produced material samples were in lightweight concrete class according to thermal and mechanical properties. As to the observations, tests, experiments, and evaluations on lightweight concrete material samples, it was concluded that the lightweight concrete with tragacanth and pumice additive can be used as a coating and dividing material in buildings because of its insulating features.
Keywords: Pumice; tragacanth; thermal Conductivity; compressive Strength; abrasion Loss; water absorption